Students Interpersonal Trust in the Context of Collaborative Group Learning - Pertiwi, Talitha Lintang; Alwan, Faiz Fatihul; Kuswardani, Hasna Pratiwi; Karim, Chamilul Hikam Al (Humanitatis : Journal of Language and Literature, 2025)
Collaborative group learning, commonly referred to as group work, is widely applied in higher education to enhance students teamwork, communication, and problem-solving skills. However, the success of this learning model depends heavily on interpersonal trust among group members. This study aimed to explore students interpersonal trust toward their group members in academic settings. Using a descriptive quantitative design, data were collected from 257 students across various universities in Indonesia through snowball sampling. Interpersonal trust was measured using the Interpersonal Trust Scale, developed based on Rotters framework, which demonstrated strong psychometric properties (item discrimination indices: 0.3330.865; reliability coefficient: 0.947). The findings revealed that most participants demonstrated high levels of interpersonal trust, with reliability as the dominant aspect, indicating that students could rely on and entrust tasks to their peers. Furthermore, no significant differences were found across demographic factors, including gender, field of study, and university status. These results highlight the central role of reliability in shaping effective group work and suggest that lecturers and curriculum developers should foster supportive learning environments, establish clear group norms, and integrate communication and conflict resolution training. This study contributes both theoretically and practically to the literature on interpersonal trust in higher education. It suggests that future research should employ more complex methods and comparative approaches, particularly between online and offline learning contexts, to better understand the dynamics of trust in collaborative learning.